Bandwidth Control with QoS tools Through the Controller (Ryu) and (openflow) Protocol - القبيلي, مثنى; حسن, بشرى (Latakia University Journal -Engineering Sciences Series, 2022)
The increased traffic on the network and the inability of the traditional networks with their current structure to deal with the fast traffic on the network, led to the emergence of a new dynamic flexible structure programmed according to the behavior of the data flow across the network, this structure is software defined networks SDN, which gives flexibility in controlling network resources by separating the control plane from the data plane. The problem of end to end QUALITY OF SERVICE in traditional networks is an ongoing problem. Many researchers have proposed a set of solutions, but most of them either failed or their solutions were not implemented, and software defined networks came as a solution to reduce the limitations in Current traditional network architectures SDNs can help provide QoS in a variety of ways due to some of their features such as the concept of per flow control and multi-header fields based routing In this research, we present two methods of controlling bandwidth using the open flow protocol and the RYU controller, namely the quality of service for each flow (per-flow Qos), which is able to precisely control the quality of service for each flow, but with the increase in the number of flows, this will lead to an increase in the rules or The flow entries in the flow table of the switch that are set to control the bandwidth and thus this method is not scalable and unable to handle with many flows, so the second method was used where the flows are divided into several categories depending on the value (DSCP), (DSCP) is 8 bits In the (ipv4) header within the (type of service TOS) field or within the (traffic class) field in the (ipv6) header, Then queues are allocated by service class that includes a group of flows that have the same required QoS level. And we explain how these methods can control the bandwidth According to the user's need and thus the control of network resources and the optimal use of them.